He lived for the sake of people. To the 180th anniversary of the Yekaterinoslav zemstvo doctor V.T. Skrylnikov (1837-1898). - Pisarenko, Yu. G. (Medicni Perspektivi, 2017)
For the first time the article introduces to the reader biography of one of the founders of the Yekaterinoslav Medical Society, a local doctor, author of numerous scientific papers on medicine and hygiene VasiliyTimofeevich Skrylnikov. The first part provides previously unknown details about his origin, the work as the head of the free zemstvo clinic, highlights his proposals in the field of sanitary service of the city Yekaterinoslav, wide publishing activities. The aspects of V.T. Skrylnikov’s service on guardianship of orphans, and the initiative to create Yekaterinoslav Department of Russian society of public health are touched upon.